Development of an advanced nano-satellite (VELOX-IV)-attitude control system - Yap, Kelvin Wei Quan (2016)
Nanosatellite is a term used to describe artificial satellite with mass between 1 to 10 kilograms. Attitude Control System (ACS) is a component within the satellite that controls and stabilises the attitude of the satellite. The attitude of satellite refers to the orientation of the satellite in space. An efficient ACS would orientate the satellite such that the desired face of the satellite points accurately to the target object with minimal error. For instance, orientate the satellite accurately in an angle such that the solar panel is facing the Sun to harvest the maximum amount of power from the sunlight energy. In this thesis, the ACS with unconstrained Model Predictive Control (MPC) strategy was simulated and experimented. The satellite system performance was being analysed as the MPC parameters, namely the prediction (Np) and control (Nu) horizon, varied. The experimental results show that the average steady error generally decreases with increasing Np value, for Nu > 1. Greater Np provides better prediction of system response, thus resulting in an effective control action being implemented. Also the experimental results show constant overshoot, which is due to the constraints of the physical components that are not being considered in the MPC strategy. The current test-bed used to determine the efficiency of the satellite in tracking moving object was modified for various reasons. The air bearing system, which is used to simulate the satellite, wobbles when stabilises because during the calibration of the sun senor, the rotational axis of the rate table is misaligned with the sensor axis. Moreover, the solar simulator is placed at a stationary position instead of simulating a moving object. Ultimately, a 2-axis gimbal system was used to mount the solar simulator in order to overcome the above-mentioned constraints. These findings and implementations show the importance for proper adjustment of control parameters in order to achieve good system performance. Moreover, it highlights the significance of having a proper test-bed to determine the efficiency of the satellite’s ACS in tracking target object under near-space conditions.